A comprehensive model of basin ecological compensation funds—A case study of the Yellow River Basin in China - Zhang, Jie; Zou, Jinwen; Zhang, Kaiyi (Frontiers in Environmental Science, 2023)
The key issue in the ecological compensation mechanism in the Yellow River Basin (YRB) is the allocation of ecological compensation funds, which need to be optimized to maximize the comprehensive benefits of compensation. In this study, a comprehensive allocation model for ecological compensation funds in the YRB was constructed using the “doughnut” framework. A pre-allocation model was used to enhance the ecological benefits and quantifies the ecological value created by the compensated subjects. A pre-allocation scheme was then determined using the pre-allocation model. The optimal allocation model focuses on benefit sharing and sets a socioeconomic discrimination index system to optimize the pre-allocation scheme. Then, an empirical analysis was conducted using data from 28 regions in the upstream YRB from 2016 to 2020. The results showed that in the pre-allocation scheme, the proportion of funds was low in the west and high in the east. Each region received compensation funds based on the ecological benefits they provide. In the optimal allocation scheme, the proportion of funds received by the central and western regions in the upstream YRB should be higher, while the proportion of funds received by provincial capitals and economically strong cities should be lower, which is in line with the actual development situation in the upstream YRB. The final scheme can effectively meet the objectives of basin-wide sustainable development, ecological benefits enhancement, and benefit sharing in the YRB. This can help achieve basin-wide sustainable development and provide a reference for determining ecological compensation fund allocation schemes in other basins.